Investigations of batch fluctuation regarding tribological conditions in series production of car body parts - Hansen, B.; Wagner, P.; Purr, S.; Merklein, Marion (International Journal of Material Forming, 2021)
Fluctuations of material properties are one reason for the occurrence of cracks and waviness in series production of car body parts. Especially fluctuating tribological conditions have an effect on the friction behavior and thus on the material flow. So far fluctuating material properties are not considered in the standard FE-simulation and consequently not in the tool design. In order to enhance the accuracy of the simulation result and thus improve the tool design regarding a robust process, the appearance of batch fluctuations has to be consistently understood. Therefore, the impact of varying lubricant quantities and roughness have been investigated. Several batches have been analyzed to identify the main influencing parameter regarding the friction behavior. Flat strip-drawing tests have been performed to determine the friction coefficient. The investigations have been performed by using material from the series production, as delivered. Since the amount of lubricant turns out to be the main influencing factor, the characteristics and appearance of the lubricant distribution has been analyzed in a further step. The analysis has shown that the distribution of the lubricant changes within one coil over the coil width and length. In addition, the time of storage has been identified as one main influencing factor on the homogeneity of the lubricant distribution over the coil width. Based on these findings, a method has been developed to map the series production conditions regarding the friction conditions in the simulation. Hence, simulations were performed using a side frame blank with different friction conditions, to investigate the impact on the forming result. The results reveal that by considering realistically existing tribological conditions, more scrap is to be expected compared to the conventional simulation. This leads to the conclusion that previous simulation results are too optimistic. Consequently, the introduced method offers the potential to optimize the tool design by considering fluctuating tribological conditions already in the process of development. Thus, it is possible to reduce scrap and increase productivity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Friction; Material; Tribology